Hubungan Antara Tingkat Stres Dengan Hipertensi Di Dusun Danurojo Desa Gondoruso Kabupaten Lumajang - Dedik Budiyanto (PROFESSIONAL HEALTH JOURNAL, 2023)
Introduction : Stress level is a mental, physical and emotional disorder, due to stress, the heart pumps blood too fast so that it can cause hypertension. The purpose of this study was to determine the relationship between stress levels and hypertension in Danurojo Hamlet, Gondoruso Village, Lumajang Regency. Methods: The research design used a correlative design with a cross sectional approach. The study population was 44 people with hypertension in Danurojo Hamlet, Gondoruso Village, Lumajang District and the research sample was 44 respondents with the determination using Total Sampling. Data collection techniques used instruments in the form of a stress level questionnaire and blood pressure checks. Result: The data analysis method used Spearman Rank test. The results showed that most of the 31 (70.5%) respondents experienced severe stress levels and most of the 24 (54.5%) respondents experienced stage 2 hypertension. Discussion and Conclusion : The results of the Spearman Rank test showed that there was a relationship between stress levels and hypertension in Danurojo Hamlet, Gondoruso Village, Lumajang District, obtained p value = (0.000) < (0.05), meaning that someone who experiences severe stress levels can cause stage 2 hypertension. Latar belakang: Tingkat stres merupakan gangguan keadaan mental, fisik dan emosional, akibat stres jantung memompa darah terlalu cepat sehingga bisa menyebabkan hipertensi. Tujuan penelitian ini yaitu untuk mengetahui hubungan antara tingkat stres dengan hipertensi di Dusun Danurojo Desa Gondoruso Kabupaten Lumajang. Metode: Desain penelitian mengunakan desain korelatif dengan pendekatan cross sectional. Populasi penelitian sebanyak 44 penderita hipertensi di Dusun Danurojo Desa Gondoruso Kabupaten Lumajang dan sampel penelitian sebanyak 44 responden dengan penentuan menggunakan Total Sampling. Teknik pengumpulan data menggunakan instrumen berupa lembar kuesioner tingkat stres dan pemeriksaan tekanan darah. Hasil : Metode analisis data yang di gunakan yaitu uji Spearman Rank. Hasil penelitian membuktikan sebagian besar 31 (70,5%) responden mengalami tingkat stres berat dan sebagian besar 24 (54,5%) responden mengalami hipertensi tahap 2. Kesimpulan: Hasil uji Spearman Rank menunjukkan terdapat hubungan antara tingkat stres dengan hipertensi di Dusun Danurojo Desa Gondoruso Kabupaten Lumajang didapatkan p value = (0,000) < (0,05), artinya seseorang yang mengalami tingkat stres berat bisa menyebabkan kejadian hipertensi tahap 2.